Design, synthesis and antitumor activity evaluation of trifluoromethyl-substituted pyrimidine derivatives. (1st November 2021) - Liu, Limin; Wang, Zhengjie; Gao, Chao; Dai, Honglin; Si, Xiaojie; Zhang, Yang; Meng, Yaqi; Zheng, Jiaxin; Ke, Yu; Liu, Hongmin; Zhang, Qiurong
Graphical abstract: Abstract: In order to find efficient new antitumor drugs, a series of novel trifluoromethyl-substituted pyrimidine derivatives were designed and synthesized, and the bioactivity against four human tumor cells (PC-3, MGC-803, MCF-7 and H1975) was evaluated by MTT assay. Compound 17v displayed potent anti-proliferative activity on H1975 (IC50  = 2.27 μΜ), which was better than the positive control 5-FU (IC50  = 9.37 μΜ). Further biological evaluation studies showed that compound 17v induced apoptosis of H1975 cells and arrested the cell cycle at G2/M phase. Furthermore, compound 17v induced H1975 cells apoptosis through increasing the expression of pro-apoptotic proteins Bax and p53 and down-regulating the anti-apoptotic protein Bcl-2. In addition, compound 17v was able to be tightly embedded in the active pocket of EGFR. In summary, these results demonstrated that compound 17v has a potential as a lead compound for further investigation.